The Effect of Working Capital Turnover, Cash Turnover and Inventory Turnover on The Profitability of Companies Listed on The Indonesian Stock Exchange - Abidatul Khoiroh; Alkusani Alkusani; Wasti Reviandani (Universitas Muhammadiyah Gresik, 2022)
This study aims to test working capital turnover, cash turnover and inventory turnover on the profitability of manufacturing companies in the food and beverage subsector. By using 30 samples of the company's annual financial statements to analyze the effect of working capital turnover, cash turnover and inventory turnover on the profitability of companies listed on the Indonesia Stock Exchange in 2017-2019. This test is done by using multiple linear regression. The regression results show that partially working capital turnover has a significant and significant effect on profitability with a level of 7.1%. While the cash turnover and inventory turnover variables have no effect on profitability. This research can be used by companies in determining performance and making managerial decisions based on financial statements. This study has limitations only on financial statements for companies.